Case Report: Preoperative ultrasonographic diagnosis of accessory cavitated uterine malformation: a case series report and narrative review - Shen, Tingting; Yuan, Hongxia; Cao, Hong; Liu, Junhong; Duan, Xiangling; Chen, Shasha; Tian, Rong; Duan, Xingxing (Frontiers in Oncology, 2025)
ObjectivesAccessory cavitated uterine malformation/mass (ACUM) is an extremely rare uterine malformation that is frequently misdiagnosed preoperatively. This study presents three ACUM cases accurately diagnosed by preoperative ultrasonography in our hospital. Through a comprehensive literature review, we systematically summarize its characteristic sonographic findings and key points for differential diagnosis, aiming to enhance sonographers’ recognition of ACUM and improve the accuracy of preoperative diagnoses.Materials and methodsWe collected three ACUM cases diagnosed in our hospital from January 2023 to April 2025. The general clinical information, ultrasound and radiological findings, pathological reports, and surgical records were retrospectively analyzed. A total of 13 previous literature reports, including a total of 39 ACUM cases, were also reviewed.ResultsThe comprehensive analysis of 39 previously reported ACUM cases and three confirmed cases from our institution revealed the following: 1. The mean age of the ACUM patients was 25.9 ± 6.5 years. 2. The primary clinical presentations of ACUM consisted of dysmenorrhea (83.3%) and lower abdominal pain (47.6%), with additional findings of dyspareunia (9.5%), difficult defecation (2.4%), and primary infertility (2.4%). 3. The ultrasonographic features are as follows: a) ACUM typically appeared as a thick-walled cystic mass not connected to the uterine cavity. b) The mean maximum outer diameter was 34.3 ± 11.7 mm (range 16–64 mm), with a median of 31.5 mm.c) The cyst was often surrounded by a homogeneous thick muscular layer (83.3%) and exhibited ring-like or semi-ring-like vascular signals (19.0%). d) The cystic cavity typically exhibited a ground-glass appearance (64.3%). e) Only seven cases (16.7%) displayed clearly identifiable endometrial lining on ultrasound examination. 4. Details of diagnostic accuracy are as follows: a) The preoperative ultrasound diagnostic concordance rate was 47.6%. b) ACUM was most frequently misdiagnosed as uterine leiomyoma (28.6%) and cystic adenomyosis (21.4%), with one case (2.4%) misdiagnosed as type II rudimentary horn uterus.ConclusionACUM is an exceedingly rare lesion that is particularly prone to misdiagnosis. ACUM should be considered in young female patients with severe dysmenorrhea and imaging findings of a normal uterine cavity and bilateral ovaries and a thick-walled cystic mass within the myometrium that does not communicate with the uterine cavity. Familiarity with the ultrasound manifestations of ACUM can help sonographers make timely and accurate diagnoses, assisting clinicians in choosing appropriate treatment methods and alleviating patient suffering.